PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF STRUKTURAL TIPE THREE STAY ONE STRAY (TSOS) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 4 TAMBUSAI - Simanjuntak, Hotdiana; -, Arcat; -, Nurrahmawati (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
The purpose of this research was to know the effect of three stay one stray cooperative learning model to the studentsâ result in mathematics learning. The kind in this research was Quasi Experimental by using the randomized posttest-only control group design. Based on the research know that the average score in experiment class is 85.20 and in the control class is 49.6. The result of t-test obtained thitung= 8.467 and ttabel= 2.0211. Because the thitung>ttabel, it mean that H0 was rejected. Based on the hypothesis, the result could be eoneluded that there was the effect of Three Stay One Stray (TSOS) cooperative learning model to the studentsâ result in mathematics learning. Keyword: The effect, Three Stay One Stray (TSOS), the result of learni